Molecular characterisation of human peripheral blood stem cells - Ruzanna Ab Kadir; Shahrul Hisham Zainal Ariffin; Rohaya Megat Abdul Wahab; Sahidan Senafi (South African Journal of Science)
Peripheral blood mononucleated cells consist of haematopoietic stem cells (HSCs) and mesenchymal stem cells (MSCs). To date there is no well-defined isolation or characterisation protocol of stem cells from human adult peripheral blood mononucleated cells. Our aim in this study was to isolate and characterise mononucleated cells from human peripheral blood. Peripheral blood mononucleated cells were isolated using the Ficoll-Paque density gradient separation method and cultured in complete medium. After 4 days of culture, adherent and suspension mononucleated cells were separated and cultured for 14 days in an in-vitro culture selection. Stem cells in the isolated mononucleated cells were characterised using a multidisciplinary approach which was based on the expression of stem cell markers, morphology and the capacity to self-renew or proliferate and differentiate into specialised cells. Reverse transcription polymerase chain reaction was used to identify the expression of an HSC marker (signalling lymphocytic activation molecule family member 1, SLAMF1) and a MSC marker (CD105). Results revealed that adherent mononucleated cells were positive for MSC markers, whereas mononucleated cells in suspension were positive for HSC markers. The isolated adherent and suspension mononucleated cells were able to maintain their stem cell properties during in-vitro culture by retaining their capacity to proliferate and differentiate into osteoclast and osteoblast cells, respectively, when exposed to the appropriate induction medium. The isolated mononucleated cells consisted of suspension HSCs and adherent MSCs, both of which have the capability to proliferate and differentiate into mature cells. We have shown that suspension HSCs and adherent MSCs can be obtained from an in-vitro culture of peripheral blood mononucleated cells.